SYNTHESIS, CHARACTERIZATION, AND PHOTOCATALYTIC PROPERTIES OF WO3/TIO2 NANOCOMPOSITES VIA GREEN SYNTHESIS METHODS USING LEMONGRASS EXTRACT - Tanzeela Faiz; Tahira Bibi; Delawar Ashraf; Ramzan Ullah; Huma Arif; Asadullah Talib; Muqddas Hameed; Durr Muhammad (Spectrum of Engineering Sciences, 2025)
This research presents a green synthesis route for pure TiO₂, WO₃, and TiO₂/WO₃ nanocomposites using lemongrass (Cymbopogon flexuosus) extract as a natural reducing and stabilizing agent. Characterization techniques such as SEM, EDX, FTIR, XRD, and UV-Vis spectroscopy confirmed the morphology, purity, structural integrity, and optical properties of the materials. Band gap energies were found to be 3.01 eV (TiO₂), 2.92 eV (WO₃), 2.81 eV (TiO₂/WO₃ 2:1), and 2.49 eV (TiO₂/WO₃ 1:1). Photocatalytic efficiency was evaluated by degrading methylene blue (MB) under solar light. The 1:1 TiO₂/WO₃ composite demonstrated superior degradation performance. This study supports the application of green-synthesized nanocomposites in environmental remediation.